KOMPOSISI VEGETASI DASAR PADA AREAL BEKAS TAMBANG BATUBARA DI KECAMATAN KAMANG BARU KABUPATEN SIJUNJUNG - Panuti, Setia - (STKIP PGRI Sumbar, 2014)
Coal mining activity in Kamang Baru has been carried out. Coal mining activity has positive and negative impact. One of negative impact is causing the annoyance of vegetations and conditions circles changes in around of mining. New plants can grow in coal mined land, the plants is like cover growns. The cover growns fungtions are the withstand blows rain and runoff thus minimize erotion. The purpose of the research are to know of the vegetations compositions and circles conditions in coal mined land. The cover growns sampling conducted use the purposive sampling. The result of the research is 18 species founds in to 14 families from 893 individuals. Highest KR is Pennisetum polystachyon (L.) Schult (48,264%), lowest KR is Muntingia calabura L. and Mimosa pigra L. (0,112 % ), highest FR is Pennisetum polystachyon (L.) Schult (15,873 %), lowest FR is Blechnum sp., Muntingia calabura L., Merremia umbellata (L.) Hallier f., Mimosa pigra L., Chromolaena odorata (L.) R.M.King. & H.Rob. (1,587%), Hâ is 0,775. Circles factors measuring is air temperature (220 - 390 C), air humidity (31 â 78 %) soil temperature (290 â 390 C), soil humidity (1 - 2%), pH (6,3-7,5), soil water content (3,3-9,4 %).